Prevalence of Depressive Symptoms and Related Factors in Japanese Employees as Measured by the Center for Epidemiologic Studies Depression Scale (CES-D). - Fushimi, Masahito; Saito, Seiji; Shimizu, Tetsuo (Community Mental Health Journal, 2013)
This study aimed to examine the prevalence of depressive symptoms and related factors in Japan. For this purpose, a questionnaire including the Center for Epidemiologic Studies Depression Scale (CES-D) was administered to employees from Akita prefecture, Japan. The cutoff point for CES-D scores was 16 or above (high scorers). We analyzed the results of this survey in order to identify relationships between the prevalence of high scores on the CES-D, sociodemographic status, and employment-related variables. In total, 2,220 employees-of whom 1,069 were men and 1,151, women-satisfactorily responded, and their responses indicated that 45.0 % (41.4 % for men, 48.2 % for women) had high scores on the CES-D. The identified sociodemographic and occupation-related factors from the binomial multivariate logistic regression for high scorers were as follows: a high risk of depression was associated with being women, short and/or long sleep durations, the occasional consumption of alcohol in men, and professional work and over 8 h of work per day in women. Older age groups and non-smoking women were associated with a lower risk. These results can be used in the future as CES-D benchmark values, and might be useful in predicting the occurrence of depressive disorders.